One true king - Chainani, Soman (Chainani, Soman. School for Good and Evil, 2020)
The fairy tale of Sophie and Agatha comes to a dramatic conclusion in this sixth and final book of Soman Chainani's New York Times bestselling fantasy series. Who will sit on Camelot's throne and rule the Endless Woods? Who will be the One True King?